Dose Comparison Study of Allogeneic Mesenchymal Stem Cells in Patients With Ischemic Cardiomyopathy (The TRIDENT Study). Issue 11 (10th November 2017) - Florea, Victoria; Rieger, Angela C.; DiFede, Darcy L.; El-Khorazaty, Jill; Natsumeda, Makoto; Banerjee, Monisha N.; Tompkins, Bryon A.; Khan, Aisha; Schulman, Ivonne H.; Landin, Ana Marie; Mushtaq, Muzammil; Golpanian, Samuel; et al.
Abstract : Rationale: : Cell dose and concentration play crucial roles in phenotypic responses to cell-based therapy for heart failure. Objective: : To compare the safety and efficacy of 2 doses of allogeneic bone marrow–derived human mesenchymal stem cells identically delivered in patients with ischemic cardiomyopathy. Methods and Results: : Thirty patients with ischemic cardiomyopathy received in a blinded manner either 20 million (n=15) or 100 million (n=15) allogeneic human mesenchymal stem cells via transendocardial injection (0.5 cc per injection × 10 injections per patient). Patients were followed for 12 months for safety and efficacy end points. There were no treatment-emergent serious adverse events at 30 days or treatment-related serious adverse events at 12 months. The Major Adverse Cardiac Event rate was 20.0% (95% confidence interval [CI], 6.9% to 50.0%) in 20 million and 13.3% (95% CI, 3.5% to 43.6%) in 100 million ( P =0.58). Worsening heart failure rehospitalization was 20.0% (95% CI, 6.9% to 50.0%) in 20 million and 7.1% (95% CI, 1.0% to 40.9%) in 100 million ( P =0.27). Whereas scar size reduced to a similar degree in both groups: 20 million by −6.4 g (interquartile range, −13.5 to −3.4 g; P =0.001) and 100 million by −6.1 g (interquartile range, −8.1 to −4.6 g; P =0.0002), the ejection fraction improved only with 100 million by 3.7 U (interquartile range, 1.1 to 6.1; P =0.04). New York Heart Association class improved at 12 months in 35.7% (95% CI, 12.7% to 64.9%) in 20 million and 42.9% (95% CI, 17.7% to 71.1%) in 100 million. Importantly, proBNP (pro-brain natriuretic peptide) increased at 12 months in 20 million by 0.32 log pg/mL (95% CI, 0.02 to 0.62; P =0.039), but not in 100 million (−0.07 log pg/mL; 95% CI, −0.36 to 0.23; P =0.65; between group P =0.07). Conclusions: : Although both cell doses reduced scar size, only the 100 million dose increased ejection fraction. This study highlights the crucial role of cell dose in the responses to cell therapy. Determining optimal dose and delivery is essential to advance the field, decipher mechanism(s) of action and enhance planning of pivotal Phase III trials. Clinical Trial Registration: : URL:http://www.clinicaltrials.gov . Unique identifier: NCT02013674.